HRD climate: the conceptual framework - Mishra, Padmakali; Bhardwaj, Gopa (2002)
No other management concept has enjoyed such a high profile in recent times as Human Resource development (HRD). Research, experimentation, and experience in the field of HRD have grown enormously in the past two decades, which symbolize the recognition of importance of people's competency development. The present paper seeks to present a conceptual framework for understanding the meaning and dimensions of HRD climate. It also discusses how HRD climate is different from the well-researched construct of organisational climate. The paper further provides a brief review of studies relating to prevailing HRD climate in Indian industrial organisations. Finally, it raises certain issues concerning the need for evaluating HRD climate. - Reproduced.
Keywords: Human resources development